9. PERAN PEMERINTAH PROVINSI JAWA TENGAH DALAM MEMBERIKAN PERLINDUNGAN PREVENTIF TERHADAP TENAGA KERJA WANITA (TKW) YANG AKAN DIBERANGKATKAN KE LUAR NEGERI - Lusia Astrika (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
The Government has a duty to foster job protection for Indonesian workers, and do not distinguish between male workers-male and female workers. Including to provide preventive protection. Preventive protection in this case is the provision of protection to the Labor Women (TKW) during the period prior to departure abroad. This study is a descriptive type, using explanatory case study method. Based on the research that has been done, the Central Java Provincial Government already provide preventive protection for Labor Women who will be flown out of the country, as evidenced by the PAP program and Housemaid. In this case the Central Java Provincial Government has run function planning, budgeting, organizing, and coordinating. But both programs are not integrated gender mainstreaming (PUG) in the curriculum. In the implementation of inter-agency partnerships related to preventive protection for migrant workers to be dispatched abroad, relations with the Central Java Provincial Government while the relationship is associative BLKLN Central Java Provincial Government (Manpower) with BP3TKI are parallel. In exercising coordinating, planning, budgeting, and organizing the government should adjust to the conditions and needs of the Labor Women (TKW), not merely to fulfill the functions and role of institutions only.